On Angela Carter’s Subversive Panorama - Çelik Ekmekçi (Nalans, 2019)
Angela Carter uses subversive narrative techniques and qualities in producing her groundbreaking works and establishing her demythologising and (de)philosophising panorama, which is named ‘The Carteresque’. While establishing her narration, Carter uses major narrative qualities such as magic realism, intertextuality, fetishism, and grotesque respectively. On the basis of her viewpoint on feminism, Carter paves the way for her subversive politics and her autonomous narrative qualities are shaped accordingly. This study explores ‘Intertextuality’ as one of the major literary ways of Carterian expression and clarifies Carter’s politics of intertextuality with its theoretical background.